Продолжение и аппроксимация субгармонических функций в полуплоскости. Невозможность продолжения плюрисубгармонических функций - Рашковский, А.Ю.; Ронкин, Л.И. (Український математичний журнал, 1994)
Будуються різного роду продовження субгармонічної в півплощині функції на всю площину. Одержані результати застосовуються для апроксимації субгармонічної функції скінченного порядку в півплощині логарифмом модуля цілої функції. Показано, що задача продовження плюрисубгармонічної функції може мати розв'язку. Various extensions to the whole plane of a subharmonic function defined on a half-plane are constructed. The results obtained are alpplied to approximation of a subharmonic function of finite order by the logarithm of the modulus of an entire function. It is shown that a problem of the extension of plurisubharmonic functions may have no solution.